Bio-liquefaction/solubilization of lignitic humic acids by white-rot fungus (Phanerochaete chrysosporium) - Elbeyli, Iffet Yakar; Palantoeken, Arzu; Piskin, Sabriye; Peksel, Ayseguel; Kuzu, Huriye (TAYLOR & FRANCIS INC, 2006)
Humic acid samples obtained from lignite were liquefied/solubilized by using white-rot fungus, and chemical characterization of the products was investigated by FTIR and GC-MS techniques. Prior to the microbial treatment, raw lignite was oxidized with hydrogen peroxide and nitric acid separately, and then humic acids were extracted by alkali solution. The prepared humic acid samples were placed on the agar surface of the fungus and liquid products formed by microbial affects were collected. The products were analyzed and the chemical properties were compared. The results show that oxidation agent and oxidation degree affect composition of the liquid products formed by microbial attack.
Keywords: lignite; humic acid; white-rot fungus; liquefaction; solubilization; LOW-RANK COAL; NEMATOLOMA-FROWARDII B19; MANGANESE PEROXIDASE; ENZYME-SYSTEMS; SPANISH COALS; DEPOLYMERIZATION; MICROORGANISMS; DEGRADATION; MECHANISMS; Energy & Fuels; Engineering; Environmental Sciences & Ecology